Current challenges in Central Asian water governance and their implications for research, higher education, and science-policy interaction - Iskandar Abdullaev; Aliya Assubayeva; Ihtiyor Bobojonov; Nodir Djanibekov; Ines Dombrowsky; Abror Gafurov; Ahmad Hamidov; Elke Herrfahrdt-Pähle; Barbara Janusz-Pawletta; Rovshen Ishangulyyev; Ulan Kasymov; Bakhrom Mirkasimov; et al. (Central Asian Journal of Water Research, 2025)
Political tensions over water management in the Central Asia region have intensified since the Soviet era, as ecological issues like the drying Aral Sea and seasonal hydropower disruptions impact downstream countries. The paper discusses the region's water governance challenges, including climate-induced uncertainties, water resource demands, and the limited capacity of local research institutions. While Central Asia's governments have initiated reforms, including new infrastructure and agreements, resilience in water management remains underdeveloped. The paper also explores the role of higher education institutions in fostering capacity-building for sustainable governance, emphasizing the need for local expertise and regional collaboration. The proposed establishment of a Central Asian water research platform aims to enhance science-policy integration, promote sustainable water governance, and support informed regional cooperation on transboundary water issues.
Keywords: 630; water governance; water management; Central Asia; transboundary; water cooperation